THE GROWTH AND SURVIVAL STUDY OF PEARL OYSTER SEEDS (Pinctada maxima) BASED ON THE DIFFERENCE DEPTH LEVELS IN KAPO NTORI BAY, BUTON ISLAND - M.S. Hamzah; Bisman Nababan (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2009)
Extreme change in sea surface temperature that might be influenced by global warming has negative impact on the pearl shell farming in Kapontori Bay.This change occurred above tolerance threshold for pearl shell juvenile survival at 3-4 cm shell wide that caused its mortality.The study was conducted from 28 February to 28 May 2008 at the Kapontory Bay,Buton island. The research aimed to identify growth and survival of pearl oyster seeds(Pinctada maxima) on differences of depth level.This research is important especially for pearl farming development in Southeast Sulawesi waters,as a reference basis in an effort to improve seedling survival of pearl oysters that are highly vulnerable to extremechange in temperature conditions. The variance analyses showed that the depth levels did not significantly affect the survival rates of the pearl oyster seeds (P>0,05). However, based on depth levels,higher survival rates (96.67%)were found on the depth of 2 m.Some environmental parameters in relation to the growth and survival rate of pearl oyster seed were discussed in this paper. Keywords:Depth levels,survival rate, growth, pearl shell, Kapontori Bay